The Influence of the Principal’s Managerial Leadership and Work Discipline on SMA Teacher’s Performance - Fransiska, Ria; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2024)
Education is the basic capital for improving the quality of good human resources and achieving success in the national development process in all fields. Education aims to provide various proactive and creative efforts by all components of the nation so that the young generation can develop optimally. School principals play an important role in efforts to mobilize teachers to have work performance, mature coordination, and leadership that is in harmony with the work environment. The aim of the research is to analyze the influence of managerial leadership, the work discipline of school principals, and the influence of both together on teacher performance in high schools throughout Banyuasin I Regency. This research was carried out at SMAN 1 Banyuasin I, SMAN 2 Banyuasin I, and SMA YP Mantra Mariana Banyuasin I Regency. This research uses descriptive analysis. The sampling methodology uses probability sampling. Research shows that the performance of teachers in high schools in Banyuasin I Regency is quite good, but there is a significant gap between the number of teachers and the number of students. The research results show that teacher performance at SMA Negeri 2 Banyuasin I is still low, with a high percentage of teachers in 2017/2018 and a low percentage of teachers in 2018/2019. This shows the need for further research regarding teacher management and teacher discipline to improve teacher performance in high schools throughout Banyuasin I Regency.